Efektifitas promosi kesehatan melalui audio visual tentang pemeriksaan payudara sendiri (sadari) Terhadap peningkatan pengetahuan Remaja putri - Ropa - Sorea; Agrina - -; Rismadefi - Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research is to determinedthe effectiveness ofhealthpromotion by audio visual about breast self examination (BSE) for increasing girl’s knowledge about BSE. The design of thisresearch is Quasy experimentdesigned by Pre-post test with control group weredivided intoexperiment groupandcontrol group. The research was conductedongirl’s inthe “SMAN 2 Pekanbaru”. The total sample are 78peoplewhowere takenby using systematic random sampling techniquesby noticing tothe inclusion criteria. Measuring instruments that usedin both groupsarequestionnairesthat have beentested for validityandrealibility. Analysisis usedunivariateandbivariateanalyzesusing independentanddependentsample ttest. The results showed there was asignificantincreasing intherate ofchange in girl’s knowledge about BSE in experimental grouphas givenhealthpromotionaboutBSE with p(0.000) < α (0,05). It means thathealthpromotionaboutBSE is effectiveforimproving girl’s knowledge about BSE. The results of this research isrecommend to every health care have to giving health promotion about BSE by audio visual to increasing knowledge about BSE. Key words : Audio visual, knowledge, health promotion, BSE